Perceptions of Global and Domestic Agricultural Issues Held by International Agricultural Journalists - Laura Kubitz; Ricky Telg; Tracy Irani; Owen Roberts (Journal of Applied Communications, 2013)
The purpose of this study was to provide baseline knowledge of the prevalent global and domestic agricultural issues, ways to educate journalists about these issues, and sources of information used when reporting about agricultural issues, according to international agricultural journalists. The executives of the International Federation of Agricultural Journalists served as this study’s population. The IFAJ is comprised of a membership of 31 countries that practice freedom of the press. A modified Delphi method with three rounds of data collection was utilized for this study. Qualitative feedback was provided by the executives in Round One. In Rounds Two and Three, quantitative feedback was used with the goal of forming consensus on the most important global issues and methods to educate journalists about these issues.A list of important domestic agricultural issues was supplied for 20 countries. The executives also generated a list of important global agricultural issues and ways to educate journalists about these issues. Important global agricultural issues included feeding a growing global population and water quality/quantity. Face-to-face methods of educating journalists were favored by the executives. The executives identified a wide variety of sources they use to report about global and domestic agricultural issues, including government agencies, farmers, universities, online sources, professional organizations, commodity group websites, and academic journals.
Keywords: issues; agriculture; global; domestic; International Federation of Agricultural Journalists; Delphi method